Decision Support System to Determine the Accuracy of Price Estimation and Processing Time in Making Plaques Using the Simple Additive Weighting (SAW) Method - Kadafi, Muhammad; Ginting, Subhan Hafiz Nanda; Purwawijaya , Ellanda (PT. Technology Laboratories Indonesia (TechnoLabs), 2024)
When in the business world an entrepreneur must have a goal to do business, namely how his business gets good profits by providing the goods and services needed to run his business process. Internet technology is currently developing very rapidly. The existence of the internet can support the expected goals to the maximum. Therefore Printing Adil Grafika is an entrepreneurial business engaged in printing. Printing Adil Grafika often experiences many obstacles in its business processes, namely frequent mistakes in making plaques in the form of price orders that do not match the capital costs in making plaques so that the company loses in buying the material, then the absence of price provisions that make only provide prices according to calculations, many complaints from customers about delays from the hour that should have been completed in making plaques, as well as many customer complaints about other errors. With these various problems, an application is needed to determine the price of the plaque processing time fund so that it matches the standard price and processing time in the printing company adil grafika. The research method used is a data collection method consisting of field research and library research while the system development method used is the simple additive weighting (SAW) method. The results of system testing using black box testing show that the system runs according to the expected results. The result is a Decision Support System to Determine the Accuracy of Estimated Price and Working Time in Plaque Making Using the Saw Method which can reduce complaints from customers and can make it easier for companies to determine the price of plaques, on time workmanship, and also follow standards in making plaques.